Role of topical steroid in primary treatment of childhood phimosis - Changole, Sanjay; Dhane, Smita; Agrawal, Nilesh (International Journal of Research in Medical Sciences, 2017)
Background: Circumcision has been the traditional treatment for phimosis, but with some controversies due to complications. The current study was undertaken to evaluate the effectiveness of topical steroid therapy as primary treatment for childhood phimosis. Methods: A prospective observational study was conducted and a total of 100 patients (age- 3 to 12 years) of phimosis were enrolled. The management consisted of topical application of 0.05% betamethasone Ointment for 4 weeks. Those with partial response were advised additional 2 weeks of therapy. Failure to treatment cases were subsequently subjected to circumcision. Results: Total 100 patients were enrolled in the study. Out of 100 patients, 9 were excluded because of non-compliance and remaining 91 patients were studied and followed up. 85 cases out of 91 (93.4%) were declared a ‘success’; while remaining 6 (6.6%) were declared ‘failure’ and were subjected to circumcision. Of the 85 successfully treated; majority (70, 82.3%) responded within 4 weeks of treatment and 15 (17.6%) responded in 6 weeks. The highest number of patients who responded to treatment within 4 weeks were < 5 years of age (54, 93.1%) (p<0.05). Conclusions: Topical steroid (0.05% betamethasone ointment) is an effective, safe, conservative and non-surgical method of primary treatment of childhood Phimosis, especially when combined with good hygiene practices of foreskin with daily retraction and cleansing.